2022
DOI: 10.1371/journal.pone.0262530
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan is not associated with increased infection risk in Pakistani and Bangladeshi populations: Findings from controlled interrupted time series analysis of UK primary care data

Abstract: Background The effect of fasting on immunity is unclear. Prolonged fasting is thought to increase the risk of infection due to dehydration. This study describes antibiotic prescribing patterns before, during, and after Ramadan in a primary care setting within the Pakistani and Bangladeshi populations in the UK, most of whom are Muslims, compared to those who do not observe Ramadan. Method Retrospective controlled interrupted time series analysis of electronic health record data from primary care practices. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Interestingly, research from the UK reported that COVID-19 infection [151] and mortality [152] did not increase during the month of Ramadan. The reason for this could be that human saliva displays anti-viral properties as previously reported [153,154].…”
Section: Health Benefit Of Fasting Salivamentioning
confidence: 99%
“…Interestingly, research from the UK reported that COVID-19 infection [151] and mortality [152] did not increase during the month of Ramadan. The reason for this could be that human saliva displays anti-viral properties as previously reported [153,154].…”
Section: Health Benefit Of Fasting Salivamentioning
confidence: 99%
“…Antibiotic prescribing patterns before, during, and after Ramadan in a primary care setting within the Pakistani and Bangladeshi populations in the United Kingdom, most of who were Muslims, were compared to those who do not observe Ramadan. 63 Retrospective controlled interrupted time series analysis of electronic health record data from primary care practices was performed. The study consists of two groups: Pakistanis/Bangladeshis and white populations.…”
Section: Infections and Inflammationsmentioning
confidence: 99%